Analysis of Factors Affecting Nurse Job Satisfaction at Murni Teguh Horas Insani Hospital Pematangsiantar in 2025 - Princess Malau; Hizkianta Sembiring (Sean Institute, 2026)
Nurse job satisfaction is an important factor that influences the quality of healthcare services, staff retention, and hospital performance. Job satisfaction is affected by various organizational and workplace factors such as salary, work environment, coworker relationships, leadership, and workload. This study aimed to analyze the factors affecting nurse job satisfaction at Murni Teguh Horas Insani Hospital, Pematangsiantar, in 2025. This research used a quantitative approach with a descriptive correlational design. The study population consisted of nurses working at Murni Teguh Horas Insani Hospital Pematangsiantar, with a sample of 42 respondents selected using total sampling based on inclusion criteria. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results showed that simultaneously salary, work environment, coworker relationships, leadership, and workload had a significant effect on nurse job satisfaction (F = 10.332; p = 0.000). Partially, leadership had a positive and significant effect on nurse job satisfaction (B = 0.688; p = 0.000) and was the most dominant factor. Meanwhile, salary, work environment, coworker relationships, and workload did not show a significant partial effect. The regression model met classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation. It can be concluded that improving leadership quality is the key factor in increasing nurse job satisfaction. Hospital management is recommended to strengthen supportive and participative leadership styles to enhance nurse satisfaction and performance.